Lock-ins to transition pathways anchored in contextualized cooperative dynamics: Insights from the historical trajectories of the Walloon dairy cooperatives. (August 2022) - De Herde, Véronique; Segers, Yves; Maréchal, Kevin; Baret, Philippe V.
Abstract: Drawing on a historical study of the Walloon dairy cooperatives, this paper analyses how complex cooperative dynamics define lock-ins in their trajectories. We consider cooperatives as firms active on markets and as structures of collective action gathering farmers-members around common strategic goals. Williamson's framework from New Institutional Economics accounts for the embeddedness of firms' strategies and governance in their wider context of development. Under the influence of this context of development, Ostrom's IAD (Institutional Analysis and Development) and SES (Social-Ecological Systems) frameworks, merged in a so-called CIS framework, capture the dynamic interplay between the components of cooperatives. Resorting to a combination between these frameworks, this paper discusses how the interplay between the components of the cooperatives' social-ecological system unfolded in the trajectories of the Walloon dairy cooperatives over the last sixty years. We uncover a double social dilemma at play. On the part of the farmers, the social dilemma anchors itself in the tension between their short-term interests as milk supplier over those of principal investor. On the part of the cooperatives' directors, the social dilemma anchors itself in the features of linking and bridging social capital in the region, unfavourable to inter-cooperative dialogue. In the Walloon Region, these social dilemma constituted a structural driver of the competition between dairy cooperatives and the subsequent inability to cooperate and invest towards successful long-term diversification pathways. We discuss how contextual factors, in particular market features, regulatory frameworks, socio-political features, and institutional support to dialogue, may aggravate, or conversely mitigate the effect of these social dilemma on cooperatives' trajectories. We call for more historically-informed studies on the impact of context on cooperative dynamics and stress the relevance of contextualized approaches to unlock prospective dynamics of collective agency in transition pathways. Highlights: A historical study on lock-ins to diversification pathways of dairy cooperatives Other drivers than economic optimization acting on the cooperatives' trajectories An interplay between the components of cooperatives as social-ecological systems Contextualized blocking mechanisms against inter-cooperative agreements Market, regulatory and socio-political context as aggravating or mitigating factors